(untitled) (Global Journal of Human-Social Science, 2020)
Today there is a great discussion about the effects that the organization of military expeditions had on the civilian population and the economy of the province of departure The issue is relevant because in order to carry them out the State must have a great capacity to mobilize resources Felipe V strove to achieve a centralized and effective government But this only achieved in the twenties of the eighteenth century In this context it is worth asking how the Bourbon state functioned between 1715 and 1720 The study of the supply of three expeditions that took place during those years can help us to better understand this process The objective of this article is to analyze three key questions what reasons did the government have when choosing a seaport as the starting point of an expedition determine the economic effects of this decision and show which social groups benefited from it